2019
DOI: 10.1186/s12870-019-1689-y
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of phosphorus efficiency in sorghum involves pleiotropic QTL for root morphology and grain yield under low phosphorus availability in the soil

Abstract: Background Phosphorus (P) fixation on aluminum (Al) and iron (Fe) oxides in soil clays restricts P availability for crops cultivated on highly weathered tropical soils, which are common in developing countries. Hence, P deficiency becomes a major obstacle for global food security. We used multi-trait quantitative trait loci (QTL) mapping to study the genetic architecture of P efficiency and to explore the importance of root traits on sorghum grain yield on a tropical low-P soil. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 65 publications
6
63
0
Order By: Relevance
“…Phosphorus (P) is one of the most vital nutrient elements in crop output and quality formation, not only presenting in major organic molecules (e.g., RNA, DNA, ATP, and membrane phospholipids) but also playing important roles in photosynthesis, energy metabolism, enzymatic reactions, and sugar metabolism (Péret et al 2011;Qiu et al 2013). P is the second most limiting nutrient for crop production after N (Bernardino et al 2019). A large amount of P fertilizer has been used to achieve higher crop yields and ensure food security worldwide (Dhillon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) is one of the most vital nutrient elements in crop output and quality formation, not only presenting in major organic molecules (e.g., RNA, DNA, ATP, and membrane phospholipids) but also playing important roles in photosynthesis, energy metabolism, enzymatic reactions, and sugar metabolism (Péret et al 2011;Qiu et al 2013). P is the second most limiting nutrient for crop production after N (Bernardino et al 2019). A large amount of P fertilizer has been used to achieve higher crop yields and ensure food security worldwide (Dhillon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, these sorghum SbPSTOL1 genes appear to modify root system morphology and architecture, leading to increases in grain yield in field studies on a low-P Brazilian soil, and also exhibited enhanced biomass accumulation and P content in sorghum landraces from West Africa using native soils. These data suggest a stable effect of the target alleles across environments and sorghum genetic backgrounds (Hufnagel et al, 2014;Bernardino et al, 2019). In maize, homologs of OsPSTOL1 that were preferentially expressed in roots and co-localized with QTLs associated with root morphology and P acquisition traits (Azevedo et al, 2015), mapped in the same region as QTLs for grain yield on a low-P soil (Mendes et al, 2014).…”
Section: Phosphorus-starvation Tolerance 1 (Pstol1) Genesmentioning
confidence: 78%
“…Plant grows adapting to P de ciency environment covers a series of gene expressions and morphophysiological events [4], such as regulation of P transporters (PTs), mycorrhizal association, phosphatase secretion, organic acid exudation and alteration in root structure under low-P conditions [5]. Studies have shown that OsPHR2, homologous to AtPHR1 in Arabidopsis, is a major transcriptional regulator of low P response in rice [6,7] which could active the Pi starvation-induced genes through binding to the P1BS (PHR1 Binding Sequence; GNATATNC) motif presented in genes' promoter region, including PHT1 members [8,9].…”
Section: Introductionmentioning
confidence: 99%